'Creativity is a skill that everyone has': analysing creative workers' self-presentations. Issue 1 (2nd January 2019) - Eikhof, Doris Ruth; Chudzikowski, Katharina
Abstract: This paper discusses the research use of creative workers' publicly available self-presentations such as documentaries or social media posts. In so doing it contributes to our understanding of how creative workers might fruitfully be researched. The paper, firstly, argues that self-presentations can provide valuable and rich insights into creative workers' self-understanding, and thus can be of interest to creative industries researchers. Secondly, using the example of a film produced by Austrian product designers, the paper then demonstrates why researchers need to consider the processes through and contexts in which self-presentations are generated. The paper explains why self-presentations may not be treated in the same way as the first person accounts traditionally generated for social science research, and presents recommendations for how self-presentations might form parts of rigorous research designs.